2018
DOI: 10.1051/matecconf/201815403003
|View full text |Cite
|
Sign up to set email alerts
|

Interaction design of automatic faucet for standard hand-wash

Abstract: Abstract. In hand-washing practice, people tend to forget to use soap and scrub for 20 seconds as stated in the standard. This paper attempts to develop an automatic faucet that is user-friendly and easy to plug in regular water pipe for standard hand-washing routine. An Interaction Design Process that aims to maximize product usability was applied during the development. The faucet utilized IR proximity sensor to detect presence of hands that would automatically commence the hand-washing process. First, it ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Hand hygiene is essential to human health and day-to-day activities. Maintaining proper hand hygiene can help reduce pathogen growth and transmission of diseases (Fitriyah et al, 2018). This activity should happen before and after handling food, eating, and using the toilet (Hantrakul et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Hand hygiene is essential to human health and day-to-day activities. Maintaining proper hand hygiene can help reduce pathogen growth and transmission of diseases (Fitriyah et al, 2018). This activity should happen before and after handling food, eating, and using the toilet (Hantrakul et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, his findings suggested that the automated dispensers may increase the rate of handwashing (Wong, 2008). Much of the literature has stated that handwashing is the most abundant task that people do every day, and the amount of water used is countless (Fitriyah et al, 2018). The WHO guidelines and other research indicates for standard handwashing procedures that one should obtain enough soap to cover all surfaces of the hand and rinse with warm water for 20 to 30 seconds, but barely 50% of the population can adhere to that standard (Fitriyah et al, 2018;WHO, n.d.).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [13,14] built a solar-powered, automated water tap prototype. The system detects human hand presence using an ultrasonic sensor and an Arduino It instructs the relay to activate the solenoid valve and allow water to flow by sending "on" and "off" commands.…”
Section: Related Workmentioning
confidence: 99%
“…According to the study by [15] they designed and implemented an automatic faucet that is user-friendly and easy to plug in regular water pipe for standard hand-washing routine. The faucet utilized IR proximity sensor to detect presence of hands that would automatically commence the hand-washing process.…”
Section: Related Workmentioning
confidence: 99%